2007
DOI: 10.3109/s10165-007-0576-9
|View full text |Cite
|
Sign up to set email alerts
|

Improved response to infliximab after leukocytapheresis in a patent with rheumatoid arthritis

Abstract: This is the first report on effective leukocytapheresis (LCAP) in an acquired infliximab (IFM) resistant patient with rheumatoid arthritis (RA). A 44-year-old Japanese woman with RA was treated with prednisolone, cyclosporine A, and methotrexate, which failed to stabilize the disease. Infliximab was then administered and the disease activity was controlled on December 2003. However, RA became active again on June 2004 so that LCAP was administered weekly for 5 weeks. After the LCAP treatment, the ACR20% respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The effects persisted even after treatment completion, with CRP level showing tendency to decrease through 4 weeks after LCAP completion. LCAP thus represented a beneficial treatment for RA, and the results of this study were not inconsistent with those of previous studies [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In this study, patients showed high disease activity prior to LCAP initiation.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…The effects persisted even after treatment completion, with CRP level showing tendency to decrease through 4 weeks after LCAP completion. LCAP thus represented a beneficial treatment for RA, and the results of this study were not inconsistent with those of previous studies [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In this study, patients showed high disease activity prior to LCAP initiation.…”
Section: Discussionsupporting
confidence: 48%
“…No other noteworthy serious adverse events were seen in our study. Though fever (n=2), headache (n=2), nausea (n=1), and blood pressure decrease (n=1) have occurred, these symptoms were usually transient as reported previously [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. (Table3) Of 85 patients who underwent LCAP treatment in this study, 51 patients achieved ACR20 at the completion of 5 treatment and they were considered as responders.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…In a report by Azuma et al., LCAP was performed a total of five times at a frequency of once a week using a CS‐100 with 3000 mL whole blood in a 44‐year‐old male RA patient with a reduced response to INF, 5 months after starting INF therapy. Decreased CRP, decreased tender/swollen joint counts, decreased DAS28‐CRP, and achievement of ACR20 were noted 1 week after completion of LCAP (14). Although the mechanism of action is unknown, the response to INF might have been restored by a decrease in the volume of TNFα‐producing cells and TNFα in the synovium due to LCAP‐induced redistribution of granulocytes and lymphocytes from the peripheral blood.…”
Section: Discussionmentioning
confidence: 99%